Rethinking One Health: Emergent human, animal and environmental assemblages. (August 2020) - Davis, Alicia; Sharp, Jo
Abstract: One Health perspectives are growing in influence in global health. One Health is presented as being inherently interdisciplinary and integrative, drawing together human, animal and environmental health into a single gaze. Closer inspection, however, reveals that this presentation of entanglement is dependent upon an apolitical understanding of three pre-existing separate conceptual spaces that are brought to a point of connection. Drawing on research with livestock keepers in northern Tanzania, in the context of the history of livestock policy in colonial and postcolonial East Africa, this demonstrates what an extended model of One Health - one that moves from bounded human, animal and environmental sectors to co-constitutive assemblages - can do to create a flexible space that is inclusive of the multiplicity of health. Highlights: We show that One Health is based on conceptual separation Colonial and postcolonial health policy in East Africa enacted this separation Critical social science forces One Health to recognise interspecies entanglements.